FORMATION OF HEALTH IN INFANTS BY METHOD OF PREVENTIVE THERAPY OF WOMEN WITH A RECURRENT HERPETIC INFECTION - M. A. Ovchinnikova; G. V. Santalova; I. S. Lipatov; Yu. V. Tezikov (Детские инфекции (Москва), 2018)
The article presents a comprehensive assessment of the health status of children in the first half of life, depending on the method of preventing recurrences of herpetic infection in women at pregravid and antenatal stages. The work used molecular-biological, immuno-enzymatic, biochemical, instrumental methods. The relationship between the frequency of recurrence of herpetic infection during pregnancy, complications of gestation and somatic pathology in children of the first half of life was noted. The results of the study confirm the beneficial effect of pre-gestational and antenatal immunocorrective and antiviral preventive therapy of relapses of the disease on the condition of the placenta complex, the course of pregnancy, mechanisms of fetoprotection for intrauterine infection with herpes simplex virus.